Calipha AL-Mustrshed Ballah 1118-1135 A.D. /513-529 A.H. The role of the Renaissance Reformation (Journal of the College of Basic Education, 2024)
The political reform of the most important cornerstones of the consolidation of government throughout the ages, the history is full of a lot of political reforms carried out by the people immortalized revolutions to the present day, the best guide is the revolution of Hussein (peace be upon him) reform, which is the well-known of revolutions reformist ever have written about a lot, but we chose of this study of personal Abbasi Calipha AL-Mustrshed Ballah reformist and the role through the awakening carried out by the Caliph and managed through which awaken determination Muslims who they were under the control of the Seljuks, in spite of showing some respect Seljuk to aside of the Abbasi calipha, but that the calipha AL-Mustrshed Ballah tried to regain his power , and he took advantage of the conflict that was going on between the House of Seljuk sons, and there \ ere el Islles between the two sides because the sultans did not liked waive on their influence , Calipha AL-Mustrshed Ballah become victim the plots hatched by the sultans. However it can be said that the Calipha challenging the Seljuk and completed the administrative and political reforms, thus he was opening the way led the independence of succession and restore its prestige individuals from obstacle cohesion in the Abbasid Caliphate.